A coupled‐cluster study on the noble gas binding ability of metal cyanides versus metal halides (metal = Cu, Ag, Au). Issue 29 (24th September 2015) - Pan, Sudip; Gupta, Ashutosh; Saha, Ranajit; Merino, Gabriel; Chattaraj, Pratim K.
<x xml:space="preserve">Abstract</x> A coupled‐cluster study is carried out to investigate the efficacy of metal(I) cyanide (MCN; M = Cu, Ag, Au) compounds to bind with noble gas (Ng) atoms. The MNg bond dissociation energy, enthalpy change, and Gibbs free energy change for the dissociation processes producing Ng and MCN are computed to assess the stability of NgMCN compounds. The Ng binding ability of MCN is then compared with the experimentally detected NgMX (X = F, Cl, Br) compounds. While CuCN and AgCN have larger Ng binding ability than those of MCl and MBr (M = Cu, Ag), AuCN shows larger efficacy toward bond formation with Ng than that of AuBr. Natural bond orbital analysis, energy decomposition analysis in conjunction with the natural orbital for chemical valence theory, and the topological analysis of the electron density are performed to understand the nature of interaction occurring in between Ng and MCN. The NgM bonds in NgMCN are found comprise an almost equal contribution from covalent and electrostatic types of interactions. The different electron density descriptors also reveal the partial covalent character in the concerned bonds. © 2015 Wiley Periodicals, Inc.